Implementasi Pivot Strategy pada Startup dalam Menghadapi Persaingan (Studi pada Startup CV. Reddone Digital) - Rayie Tariaranie Wiraguna (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2021)
The covid-19 pandemic that occurred in Indonesia had a big impact on business people in various fields. The impact felt varied, some benefited, but more people were harmed by this pandemic. One of the startup businesses that have felt the impact of the Covid-19 pandemic is CV. Reddone in Malang. This CV is a startup business that is engaged in printing, especially the printing of wedding invitations. During the pandemic, CV. Reddone has experienced many losses, due to the existence of a social distancing policy, so that many consumers do not carry out activities with many people. To overcome this problem, the strategy used is the pivot strategy. Pivots are changing strategies to steer a business into a favorable or desirable situation. The essence of this strategy is to develop the business by changing its business model but still based on the business vision itself. Pivot strategy is a strategy to change the business model so that the business can continue to run even in difficult times. By implementing this strategy, CV. Reddone Digital is currently experiencing sales growth. The strategy taken is to change the business model to a business based on digital-based information technology. One of their superior products is a digital online invitation that is very relevant to the current application of social distancing. Competitive advantage made by CV. Reddone Digital is the development of a digitalization innovation strategy for all business ideas that will be implemented.